Cabai Rawit Sebagai Alternatif Pengendalian Kultur Teknis Nematoda (Meloidogyne spp.) - I Dewa Putu Singarsa; I Made Mega Adnyana (Fakultas Pertanian, Universitas Udayana, 2023)
Nematodes (Meloidogyne spp.) cause a lot of losses to farmers cultivating Solanaceae family plants because Solanaceae family plants are host plants that are highly favored by nematodes (Meloidogyne spp.). most often grown by farmers to meet their daily needs. The aim of the study was to determine the penetration rate and fecundity level of nematodes (Meloidogyne spp.) in several plants belonging to the Solanaceae family, and to find out which host plant species are less preferred from the tested plants so that they can be used as an alternative for nematode control (Meloidogyne spp.). This study used a completely randomized design (RAL), with 4 types of treatment, each treatment was given 6 repetitions with 2 research objects so that 4 x 6 x 2 = 48 units/plant pot was obtained. The results showed that the penetration and fecundity levels of (Meloidogyne spp.) were highest in tomato plants, then in eggplant, then large chili plants and the lowest in cayenne pepper plants. So that these results can be used as an alternative crop rotation in the field and can be used to control nematodes (Meloidogyne spp.). technical culture.